Microwave characterization of breast mimicking phantom materials - Yew, Shi Chang. (2009)
This project focuses on the microwave characterization of Breast Mimicking phantom materials. Samples are fabricated by the author and measurements of the dielectric properties are performed. The recipe for the phantom materials are obtained from literatures’ and experimental results obtained are compared against those published.